The Practice of Feasting in Medieval Iceland - Martina Ceolin (Amsterdam University Press, 2022)
The practice of feasting appears recurrently in Old Norse-Icelandic literature, notably in sagas such as konungasögur (‘Kings’ sagas’) and Íslendingasögur (‘Sagas of Early Icelanders’). Having been studied as valuable ethnographic sources, these texts portray feasting primarily as an instrument of social action, an action which serves, among else, to publicly make and break bonds, notably friendship. Exemplary in this regard is Eyrbyggja saga (‘Saga of the People of Eyri’), a thirteenth-century Íslendingasaga which is typically set in Iceland from the beginning of its Settlement, in the late ninth century, up to the first decades of the eleventh century. Drawing from this saga, the practice of feasting in medieval Iceland will be described and discussed, with special reference to the historical time in which the text was probably composed.